Estrongilidos y strongyloides spp. de búfalos en el municipio Colón, estado Zulia-Venezuela. - Uzcátegui, David; Cubillán, Francisco Angulo; Gil, Marcelo; Ramírez, Adelso; Valbuena, Roselyn; Ochoa, Kelly; Aráque, Nelitza; Simoes, David (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Ver resumen pdf.